Application of supercritical antisolvent method in drug encapsulation: a review - Kalani, Mahshid; Yunus, Robiah (Dove Medical Press, 2011)
The review focuses on the application of supercritical fluids as antisolvents in the pharmaceutical field and demonstrates the supercritical antisolvent method in the use of drug encapsulation. The main factors for choosing the solvent and biodegradable polymer to produce fine particles to ensure effective drug delivery are emphasized and the effect of polymer structure on drug encapsulation is illustrated. The review also demonstrates the drug release mechanism and polymeric controlled release system, and discusses the effects of the various conditions in the process, such as pressure, temperature, concentration, chemical compositions (organic solvents, drug, and biodegradable polymer), nozzle geometry, CO2 flow rate, and the liquid phase flow rate on particle size and its distribution.